Translating vocative sentences by exclamation in the glorious Qur`an: A semantic analysis and message change - Omar, Nida S.; Mohd, Salahuddin; Kadhim, Kais A. (2012)
The present study takes place under the fifth item of this conference .It is concerned with investigation message change in vocative sentences in the glorious Qur'an when translated to English. The present study aims to find the answers to the following research question: “Do the syntactical and grammatical changes affect the quality of the rhetorical message when translating vocative sentences of Qur’anic texts [source language text (SLT)] to English [target language text (TLT)]? To achieve this aim, a componential analysis of both the SLT and the TLT is adopted to uncover the similarities and differences in the message content of both Arabic and English languages. To evaluate the message of both languages, Newmark’s approaches to translations are used in this study, including the use of his terminologies such as overtranslation, undertranslation, replacement translation, and inaccurate translation. The Qur'an and one English version are analyzed according to Katz and Fodor’s (1963) theory to observe the differences in the message of both SLT and TLT. The results of the current study show how the meaning is preserved in some occasions and lost in other occasions.